Metal Transition in Sodium–Ammonia Nanodroplets. Issue 40 (29th August 2016) - Hartweg, Sebastian; West, Adam H. C.; Yoder, Bruce L.; Signorell, Ruth
Abstract: The famous nonmetal‐to‐metal transition in Na–ammonia solutions is investigated in nanoscale solution droplets by photoelectron spectroscopy. In agreement with the bulk solutions, a strong indication for a transition to the metallic state is found at an average metal concentration of 8.8±2.2 mole%. The smallest entity for the phase transition to be observed consists of approximately 100–200 solvent molecules. The quantification of this critical entity size is a stepping stone toward a deeper understanding of these quantum–classical solutions through direct modeling at the molecular level. Abstract : When is a metal not a metal ? For more than a century, chemists have been struggling for a detailed understanding of the intriguing concentration‐dependent color change of metal–ammonia solutions from deep blue to copper‐gold. Indications for the underlying nonmetal‐to‐metal transition have now been found in photoelectron images of sodium–ammonia nanodroplets, paving the way for an atomistic description.